The Potency of Sea Urchin (Diadema setosum) Gonad on Brain Cells of White Rats (Rattus norvegicus) - Delianis, Pringgenies (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To investigate the amino and fatty acid contents in the gonad of Diadema setosum; body weight, hemoglobin count, number of neuron cells, weight and volume of brain of Rattus norvegicus, and lab rats. Materials and Methods: The contents of fatty and amino acids in gonad of D. setosum were analyzed by gas chromatography and high-performance liquid chromatography methods. The next stage of this research was carried out by administering treatments of 0.5, 1, and 1.5 g/subject/day of sea urchin gonad rations to different groups of rats. A special group of subjects were treated with fish oil was setup as well. Results and Discussion: Research on fatty acids content in dried ground sea urchin gonad resulted in the saturated fatty acids variety and content of lauric acids, myristiric acid, palmitic acid, stearic acid, archidic acid, behenic acid, and unsaturated fatty acids variety and content of palmitoleic acid, oleic acid, linoleic acid, linolenic acid, erucic acid, eicosapentaenoic acid, and docosahexaenoic acid. The analysis result of amino acid in dried ground sea urchin gonad showed that the ration contained variety and content of essential amino acids of threonine, methionine, valine, phenylalanine, I-leucine, leucine, lysine, tryptophan; semi-essential amino acid of histidine, arginine, and non-essential amino acids including aspartic acid, glutamic acid, serine, glycine, alanine, and tyrosine. The measurement result of rats showed the most significant increase in body weight with 1 g treatment group and the most significant increase in brain weight with 0.5 g treatment group. The group with 1.5 g treatment showed most amount of hemoglobin (14.67 d/dL) and most percentage of neuron cell count (36.68%). ANOVA statistical analysis of the experiment showed that there is no significant change in body weight, hemoglobin count, brain weight, and brain volume albeit that there is a notable change in the mount of neuron cells. Conclusion: It can be concluded that the administration of dried and ground D. setosum gonad resulted in the highest increase in body weight of subject rats at 1 g. The administration of 1.5 g dried and ground D. setosum gonad gave the most significant amount of neuron cells percentage and hemoglobin in subject rats.